Ember's end - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith) Green ember (Series), 2020)
The end is here. Heather and Picket face off for the last time with their tyrannical foes in this final installment of The Green Ember Series. The Mended Wood flickers dimly in the vision of the rabbits of Natalia, as they battle bravely for their survival and a hopeful future beyond.